Analisis Miskonsepsi Pemahaman Konsep Penguapan pada Konteks Air Mendidih pada Siswa Sekolah Dasar - Kris Damayanti; Dina Ratih; Kurnia Nabilah Far’hah; Delia Anjura; Dhiyaa Yolanda; Cagiva Salma; Wati Sukmawati (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Evaporation is the process of phase change from liquid to gas that can occur at low temperatures, even at room temperature. “Many people mistakenly believe that water only evaporates at 100°C. In fact, evaporation happens at the liquid’s surface, where molecules with high kinetic energy leave the surface and turn into vapor, unlike boiling, which occurs throughout the liquid at a specific temperature. This article explores the factors affecting evaporation, such as temperature, surface area, humidity, and air movement. Everyday examples of evaporation include water evaporating from a bucket, clothes drying, and dew disappearing. To address misconceptions, the article suggests simple experiments, molecular visualization models, and discussions of evaporation phenomena.” A proper understanding of evaporation is expected to increase students' interest and build a strong foundation for further learning in physics and chemistry.